Cloning and sequencing of a bile acid-inducible operon from Eubacterium sp. strain VPI 12708. - Mallonee, D H (1990)
Two bile acid-inducible polypeptides from Eubacterium sp. strain VPI 12708 with molecular weights of 27,000 and approximately 45,000 have previously been shown to be encoded by genes residing on a 2.9-kb EcoRI fragment. We now report the cloning and sequencing of three additional overlapping DNA fragments upstream from this EcoRI fragment. Together, these four fragments contain a large segment of a bile acid-inducible operon which encodes the 27,000- and 45,000-Mr (now shown to be 47,500-Mr) polypeptides and open reading frames potentially coding for four additional polypeptides with molecular weights of 59,500, 58,000, 19,500, and 9,000 to 11,500. A bile acid-inducible polypeptide with an apparent Mr of 23,500, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, was purified to homogeneity, and the N-terminal amino acid sequence that was obtained matched the sequence deduced from the open reading frame coding for the 19,500-Mr polypeptide. A short DNA segment containing the 3' downstream end of the gene coding for the 47,500-Mr polypeptide was not successfully cloned but was directly sequenced from DNA fragments synthesized by polymerase chain reaction. The mRNA initiation site for the bile acid-inducible operon was shown by primer extension to be immediately upstream from the gene encoding the 58,000-Mr polypeptide. A potential promoter region upstream from the mRNA initiation site displayed significant homology with the promoter regions of previously identified bile acid-inducible genes from Eubacterium sp. strain VPI 12708. We hypothesize that this bile acid-inducible operon codes for most of the enzymes involved in the bile acid 7 alpha-dehydroxylation pathway in this bacterium.